MODERN PORTFOLIO THEORY AND FORECAST IMPLEMENTATION USING MONTE CARLO SIMULATION IN AUTOMOTIVE FINANCING COMPANY - Fajartama, Rian
Automotive is a product that can support Indonesia’s economic improvement, especially motorcycle and car segments, which can increase the productivity of Indonesian society. The role of multifinance companies is vital for society to own a vehicle. Good efficiency is important for financing companies to remain stable in the new normal Covid-19 pandemic era, with one of the vital aspects is their financing portfolio management. Through the concept of Risk and Return, can be determined whether a risk is acceptable or what action must be taken to determine the trade-off between risk and return. Through Markowitz's Modern Portfolio Theory, optimal portfolio composition is also developed. This research aims to analyze or find optimal portfolio compositions for the Indonesian Automotive Financing Company.